High temperature corrosion and protection of materials 7 : selected, peer reviewed papers from 7th International Symposium on High Temperature Corrosion and Protection of Materials, Les Embiez, France, May 18-23, 2008 - Steinmetz, Pierre (Materials science forum, 2008)
Volume is indexed by Thomson Reuters CPCI-S (WoS). This special volume addresses fundamental and practical aspects of high-temperature corrosion and protection. It stresses that devoting attention to an understanding of the corrosion problems encountered by contemporary industry, and providing opportunities for extended interaction, could lead to approaches for improving the performance of materials and protective measures. The book is divided into the topics: I. Materials and Coatings for Gas Turbines, II. Power Boilers and Incinerators; H2 Syngas and Biofuel Production, III. HT Materials for Nuclear Processes, IV. HT Corrosion in the Processing Industries, V. HT Corrosion of Functional Materials and Coatings, VI. Fundamentals. The 131 papers covered all aspects of the development, testing and determination of mechanisms of the degradation of coatings. Continued efforts aimed at understanding the mechanisms of formation, growth and failure of protective scales (including approaches to modelling) were another major area of interest, and accounted for nearly a quarter of the papers. A further 20% of the papers are concerned with materials issues linked to current trends in power generation: specifically, oxidation in steam/water vapor, the effects of firing biomass, the use of oxy-fuel conditions, and materials issues associated with nuclear power generation. Overall, the ratio of papers addressing practical problems, to those concerned more with fundamental aspects, was approximately 2:1; which was a good reflection on the intent of the original plan. Proceedings of an international symposium held in Les Embiez, France, in May 2008, addressing fundamental and practical aspects of high- temperature (HT) corrosion and protection of materials. The two-volume set features 131 contributions organized into six sections. The first, on materials and coatings for gas turbines, examines lifetime issues, modes of failure, oxidation and hot corrosion, and trends and developments. Articles in the second section-power boilers and incinerators, H2 singas and biofuels production-deal with advanced steam conditions, fireside corrosion, oxy-firing, use of alternative fuels, gasification, high-temperature electrolysis, and thermochemical processes. The third section, HT materials for nuclear processes, addresses various types of reactors-pressurized-water, European pressured, high-temperature, very high-temperature, and fusion-supercritical water-cooled processes, and molten metals and salts. The fourth, HT corrosion in the process industries, focuses on the steel industry, electrometallurgy, glass and ceramics production, refining, and the petrochemical and chemical industries. The fifth, HT corrosion of functional materials and coatings, examines materials for automotive applications, burners, filters, and fuel cells. The final section on fundamentals addresses various mechanisms and new techniques for measurement and characterization of corrosion.